The non-structural protein μNS of piscine orthoreovirus (PRV) forms viral factory-like structures. (December 2016) - Haatveit, Hanne; Nyman, Ingvild; Markussen, Turhan; Wessel, Øystein; Dahle, Maria; Rimstad, Espen
Abstract Piscine orthoreovirus (PRV) is associated with heart- and skeletal muscle inflammation in farmed Atlantic salmon. The virus is ubiquitous and found in both farmed and wild salmonid fish. It belongs to the familyReoviridae, closely related to the genusOrthoreovirus . The PRV genome comprises ten double-stranded RNA segments encoding at least eight structural and two non-structural proteins. Erythrocytes are the major target cells for PRV. Infected erythrocytes contain globular inclusions resembling viral factories; the putative site of viral replication. For the mammalian reovirus (MRV), the non-structural protein μNS is the primary organizer in factory formation. The analogous PRV protein was the focus of the present study. The subcellular location of PRV μNS and its co-localization with the PRV σNS, µ2 and λ1 proteins was investigated. We demonstrated that PRV μNS forms dense globular cytoplasmic inclusions in transfected fish cells, resembling the viral factories of MRV. In co-transfection experiments with μNS, the σNS, μ2 and λ1 proteins were recruited to the globular structures. The ability of μNS to recruit other PRV proteins into globular inclusions indicates that it is the main viral protein involved in viral factory formation and pivotal in early steps of viral assembly.